2021
DOI: 10.1371/journal.pone.0254781
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of care for pregnancy, perinatal and newborn care at district and sub-district public health facilities in three districts of Haryana, India: An Implementation study

Abstract: Introduction Improving quality of care (QoC) for childbirth and sick newborns is critical for maternal and neonatal mortality reduction. Information on the process and impact of quality improvement at district and sub-district hospitals in India is limited. This implementation research was prioritized by the Haryana State (India) to improve the QoC for maternal and newborn care at the busy hospitals in districts. Methods This study at nine district and sub-district referral hospitals in three districts (Fari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…With increased knowledge and continuous discussions concerning care of the mothers and newborn, healthcare workers might also get more sensitised and empathic towards their patients. A recent implementation study conducted in India, also adopting the PDSA approach and facilitation to improve quality of care, could show improvements in satisfaction among women who had recently given birth similar to our results 26…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…With increased knowledge and continuous discussions concerning care of the mothers and newborn, healthcare workers might also get more sensitised and empathic towards their patients. A recent implementation study conducted in India, also adopting the PDSA approach and facilitation to improve quality of care, could show improvements in satisfaction among women who had recently given birth similar to our results 26…”
Section: Discussionsupporting
confidence: 88%
“…Though we could see an increased satisfaction after the intervention, the proportion of satisfied women both before and after was low. This despite that women tend to report more satisfied with care if interviewed early after childbirth, biased by social desirability and the joy of having a healthy baby29 and previous studies of satisfaction in Nepal and India has shown higher levels 26 30 31. We do not know why the women were not more satisfied with care but some factors can be considered.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Dados divulgados pelo Ministério da Saúde, em 2015, indicam que o índice de parto cesariano chega a 56%, portanto, se aproximando aos dados obtidos em nossa investigação (Leite et al, 2022). Notadamente, esta taxa varia entre os sistemas público 40% e privado de saúde 85% (Das et al, 2021). Essa realidade é considerada preocupante visto que a recomendação da Organização Mundial da Saúde é de uma taxa de cesarianas variando entre 10 a 15%.…”
Section: Discussionunclassified